Issues of water management in agriculture : (Comprehensive assessment of water management in agriculture, 2003)
The journal publishes papers of international significance regarding the science, economics, and policy of agricultural water management. The scope includes many topics: farm-level and regional water management, irrigation, drainage, and salinity management of cultivated areas, collection and storage of rainfall in relation to soil properties